EFFECTIVENESS OF THREE INSECTICIDES FOR THE CONTROL OF BEAN TOSTON, POSSIBLE Phyllonorycter sp (Lepidoptera: Gracillariidae) * IN NARIÑO - CORTÉS, MARÍA LUISA; CARDONA, CESAR; TRUJILLO, FERNANDO (Revista Colombiana de Entomología, 1990)
The insecticides thiocyclam-hydrogen oxalate (0.150 kg a.i./Ha), diflubenzuron (0.025 kg a.i./Ha) and Bacillus thuringiensis (0.5 kg c.p./Ha) were evaluated in farmer's fields for their efficiency in controlling the bean tentiform leaf miner, Phyllonorycter sp. (Lepidoptera: Gracillariidae). Evaluations were made before and alter the treatment of the plants, taking a sample of 100 leaflets per plot. The nereistoxin thiocyclam-hydrogen oxalate was highly effective; diflubenzuron and B. thuringiensis were less effective but, given their moles of action, these products could be utilized in an integrated pest management program in which natural control by Apanteles sp. could play a role.